Early predictions of hypoxic ischemic encephalopathy by umbilical cord nucleated red blood cells and lactate - Eman Abdelwahed Abdelfatah; Laila Hussein Mohamed; Nermin Ramy Mohamed; Samia Hassan Rezq (Cairo : Eman Abdelwahed Abdelfatah, 2010)
Hypoxic ischemic encephalopathy (HIE), remains a serious condition that causes significant mortality and long term morbidity. It is important to establish a simple and quick method that could be used to predict the occurrence of hypoxic ischemic encephalopathy (HIE) as early as possible by investigating the variations of nucleated red blood cells per 100 white blood cell (NRBC/100 WBC) counts and lactate levels in cord blood of the newborn
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Cord blood; Hypoxic ischemic encephalopathy; Lactate